Content analysis on the genderlect styles of the classic and remake versions of the film Temptation Island - Nablo, Clarice C.
Genderlect roles in Filipino films have been portrayed differently throughout the past decades. This can be especially observed in the classic and remade versions of the film, Temptation Island. Studying films in the context of genderlect roles could help in observing the state of equality or inequality between the genders in the society. This research utilized content analysis to determine the commonalities and differences of genderlect role between the films, along with a codebook based on the Genderlect Styles Theory by Deborah Tannen. By using the purposive sampling method, two (2) appropriate films were deliberately selected to identify whether the male and female characters maintained or deviated from their respective genderlect roles. The campy style created an assumption that the exaggerated acting aspired for its viewers to see deliberate stereotyping in characters, although Director Chris Martinez of Temptation Island (2011) said otherwise. The research findings in the classic version of Temptation Island indicate that the male characters maintained their male genderlect role; the female characters deviated from their female genderlect role. In the 2011 version, the male characters deviated from their male genderlect role; the female characters maintained their female genderlect role. It is seen that the male genderlect role is more dominant in the classic film, compared to its remade version. All characters before the enhancement of technology and film production portrayed their roles more like men who appeared to be confident and competent, while the remade version showed that male characters may also portray their roles like how females would, but still maintain some aspects of their confident and competent nature. The portrayal of women in the 1980?s appear to be just as aggressive and strong-willed as the men; while in 2011, women are stereotypically portrayed as empathetic creatures and men as people who form connections to gain romantic pleasures. It can be inferred that the stereotypical portrayal of the genders differ throughout time and that it changes with technology.